Studies on the biotechnological potential of Argentinean isolates of Waitea arvalis (Corticiales, Basidiomycota) for the biological control of phytopathogenic fungi - Melignani, Eliana; Guidobono, Juan Santiago; Rojo, Rodrigo; Levin, Laura; Barrera, Viviana Andrea (Springer, 2024)
Ten Argentinean Waitea circinata-like isolates (Corticiales, Basidiomycota) obtained from soil samples were identified to species level based on morphological features and molecular tools, and tested in order to explore their biological control abilities. Eight of them were identified as Waitea arvalis and two as W. circinata. Waitea arvalis isolates were tested as antagonists, and W. circinata isolates were used as pathogens. Most isolates performed well in in vitro antagonistic assays, inhibiting by 54–59% the growth of seven plant pathogens: Bipolaris sorokiniana, Fusarium graminearum, Fusarium oxysporum, Pythium irregulare, two different isolates of W. circinata and Sclerotium rolfsii. The most inhibited pathogen was P. irregulare (72.6%), followed by S. rolfsii (66.7%) and W. circinata (~ 65%). There was no evidence of mycoparasitism. Their capacity for chitinase, cellulase, protease and ligninase (laccase, Mn-peroxidase and lignin-peroxidase) secretion was evaluated. Most of the isolates tested positive for chitinase activity. All the evaluated W. arvalis isolates produced cellulase, protease and laccase activities, and some of them also rendered positive results for Mn-peroxidase and decolorized the dye Azure B. Isolates INTA-L003 and INTA-L005 displayed top results for cellulase activity (both in carboxymethylcellulose plate assay and in filter paper tube assay). These activities might be responsible for their better antagonistic behavior on Pythium sp. Thus, these isolates are promising as biocontrol agents and as sources of new enzymes for industrial applications. Moreover, to the best of our knowledge, this is the first citation of W. arvalis in Argentina.